The Saposin-Like Protein AplD Displays Pore-Forming Activity and Participates in Defense Against Bacterial Infection During a Multicellular Stage of Dictyostelium discoideum - Dhakshinamoorthy, Ranjani; Bitzhenner, Moritz; Cosson, Pierre; Soldati, Thierry; Leippe, Matthias (Frontiers in Cellular and Infection Microbiology, 2018)
Abstract Due to their archaic life style and microbivor behavior, amoebae may well be an intriguing source of antimicrobial peptides and proteins. Although Dictyostelium discoideum has become an interesting model for the study of host-pathogen interactions and the beginning of innate immunity in recent years, the knowledge about the arsenal that the amoebic protozoon uses to kill internalized microbes and to combat potential pathogens is limited to very few examples - at least at the protein level. Comparable to the free-living nematode and model organism Caenorhabditis elegans only, D. discoideum possesses a gene family potentially coding for an enormous number of antimicrobial proteins that structurally belong to the saposin-like protein (SAPLIP) family. SAPLIPs are also known from mammals and can fulfill a variety of biological functions as far as lipid interactions are concerned. In amoebae, it is known from Entamoeba histolytica that a SAPLIP termed amoebapore is pore-forming, antimicrobial, and cytotoxic to human cells and is considered a virulence factor, whose tertiary structure has been solved. Here, we focused with AplD on one particular member of the multifarious SAPLIP family of D. discoideum, provisionally named Apls (amoebapore-like peptides), as aplD is the only Apl gene that is reported to be primarily transcribed during the multicellular stages such as the mobile and immunologically highly interesting slug stage. Upon knock-out (KO) of the gene, aplD‾ slugs were highly vulnerable to virulent Klebsiella pneumoniae (Kp). AplD‾ slugs harbored bacterial clumps in their interior and were unable to slough off the pathogen in their slime sheaths. Re-expression of AplD in aplD‾ slugs rescued the susceptibility towards K. pneumoniae. The purified recombinant protein rAplD was able to form pores in liposomes and was also capable of permeabilizing the membrane of live bacteria. We would like to suggest that the SAPLIP family constitutes an important part of the amoebic armamentarium that acts complementarily and synergistically to allow D. discoideum to survive in its microbial world.